The principal's role in improving teacher professionalism at sman 1 donorojo, jepara regency - Tri Ani Setiorini; Widya Kusumaningsih; Soedjono (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study aims to: 1) Describe the role of the principal in planning teacher professional development, 2) Describe the role of the principal in organizing teacher professional development, 3) Describe the role of the principal in implementing teacher professional development, 4) Describe the role of the principal in supervising, evaluating, and ensuring the sustainability of teacher professional development at SMAN 1 Donorojo, Jepara Regency. This study uses a descriptive qualitative approach. The study was conducted at SMAN 1 Donorojo, Jepara Regency from February to August 2025. The research instrument was the researcher himself. Data collection techniques used in this study were interviews, observation, and documentation. Data analysis techniques consisted of data condensation, data display, and drawing conclusions and verification. The results of the study show (1) Planning: The principal's strategy in preparing a teacher professionalism development plan at SMAN 1 Donorojo Jepara includes a) analysis of teacher professionalism development needs; b) preparation of programs and strategies; c) preparation of budgets; and d) Implementation of programs. (2) Organizing: The principal's implementation in developing teacher professionalism at SMAN 1 Donorojo Jepara includes a) Formation of teams and division of tasks; Internal coordination; and c) Management of resources. (3) Implementation: Implementation of the principal's policies in supporting teacher professionalism development at SMAN 1 Donorojo Jepara includes a) Program implementation; b) Facilitation and support; and c) Direct monitoring. (4) Supervision: The principal's efforts in evaluating and ensuring the sustainability of teacher professionalism development at SMAN 1 Donorojo Jepara include a) Implementation of supervision; and b) Evaluation and follow-up.